2014
DOI: 10.1097/icu.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based review of surgical practices in endoscopic endonasal dacryocystorhinostomy for primary acquired nasolacrimal duct obstruction and other new indications

Abstract: With innovations and improvements in the endonasal approach, EN-DCR has become a viable alternative to external DCR for primary acquired nasolacrimal duct obstruction. EN-DCR has the distinct advantages of no surface scar and a lack of damage to the pump mechanism that often occur with external DCR. Recent evidence indicates a comparable success rate to external DCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…[5] With newer, more advanced instrumentation, endoscopic surgery has become more and more popular, and with increased experience, the success rates have begun to approach those of external DCR. [678] There are many variations in technique in both endonasal and external DCR. These include but are not limited to the use of endoscope, lasers, use of stents, duration of stent placement, use of mitomycin-C, use of powered tools (high speed drill and ultrasonic handpieces) vs non-powered tools (rongeurs), formation of sac/nasal mucosal flaps and whether or not they are sutured, glued, or just approximated, and the use of post-operative antibiotics and steroids (oral and/or topical).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] With newer, more advanced instrumentation, endoscopic surgery has become more and more popular, and with increased experience, the success rates have begun to approach those of external DCR. [678] There are many variations in technique in both endonasal and external DCR. These include but are not limited to the use of endoscope, lasers, use of stents, duration of stent placement, use of mitomycin-C, use of powered tools (high speed drill and ultrasonic handpieces) vs non-powered tools (rongeurs), formation of sac/nasal mucosal flaps and whether or not they are sutured, glued, or just approximated, and the use of post-operative antibiotics and steroids (oral and/or topical).…”
mentioning
confidence: 99%
“…Despite all these variables and variations, it cannot be denied that the success rates of endoscopic DCR have improved in the last 2 decades. [678] Furthermore, the improvements in techniques and instrumentation have led to increased use of this technique in SANDO, and in cases with known increased risk of failure. These include patients with prior external or endoscopic DCR (revision DCR),[89] patients with active dacryocystitis,[10] and patients with history of midfacial trauma,[11] and high dose radiation therapy.…”
mentioning
confidence: 99%
“…Although several studies have advocated marsupialisation of the mucosal flap to reduce the formation of granulation tissue, 16 not all studies have shown that doing so improves success rates 17 and we have abandoned this approach some 10 years ago. In our approach, the nasal mucosa overlying the bony ostium is removed in total.…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of endoscopic technologies, most patients have undergone endonasal (EN‐)DCR; the success rate is comparable to that of external (EX‐)DCR . Moreover, EN‐DCR has several advantages over EX‐DCR, as it is less invasive, is associated with shorter operation times, leaves no external scarring, preserves lacrimal pump function, ensures faster postoperative rehabilitation and permits the diagnosis and treatment of coexisting intranasal diseases …”
Section: Dear Editormentioning
confidence: 99%